2007
DOI: 10.1038/nature05562
|View full text |Cite
|
Sign up to set email alerts
|

An African origin for the intimate association between humans and Helicobacter pylori

Abstract: Infection of the stomach by Helicobacter pylori is ubiquitous among humans. However, while H. pylori strains from different geographic areas are associated with clear phylogeographic differentiation1-4, the age of an association between these bacteria with humans remains highly controversial5, 6. Here we show, using sequences from a large dataset of bacterial strains that, as in humans, genetic diversity in H. pylori decreases with geographic distance from East Africa, the cradle of modern humans. We also obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

44
808
1
31

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 847 publications
(884 citation statements)
references
References 23 publications
44
808
1
31
Order By: Relevance
“…As a result of the bottlenecks associated with those migrations, and subsequent isolation by distance, the pairwise genetic distances between human populations increase with distance and their genetic diversity drops with distance from sub-Saharan Africa [26]. Quantitatively similar patterns were found for H. pylori [25], and the pairwise genetic distances between H. pylori correlated strongly with genetic distances between human mtDNA sequences from corresponding geographical areas (figure 1d). The obvious interpretation was that H. pylori have accompanied humans since their out of Africa migrations about 60 kya.…”
Section: Helicobacter Pylori and Anatomically Modern Humanssupporting
confidence: 61%
See 1 more Smart Citation
“…As a result of the bottlenecks associated with those migrations, and subsequent isolation by distance, the pairwise genetic distances between human populations increase with distance and their genetic diversity drops with distance from sub-Saharan Africa [26]. Quantitatively similar patterns were found for H. pylori [25], and the pairwise genetic distances between H. pylori correlated strongly with genetic distances between human mtDNA sequences from corresponding geographical areas (figure 1d). The obvious interpretation was that H. pylori have accompanied humans since their out of Africa migrations about 60 kya.…”
Section: Helicobacter Pylori and Anatomically Modern Humanssupporting
confidence: 61%
“…A striking number of parallels were obtained between the genetic patterns and sources of native human populations and their associations with populations of H. pylori, including native Americans who migrated from Asia across the Bering Strait (hspAmerind, a subpopulation of hpEastAsia); Austronesians who migrated from Taiwan to the Pacific (hspMaori, a subpopulation of hpEastAsia; figure 1b,c); Bantu who migrated from West Africa to East and South Africa (hpAfrica1) and the original inhabitants of the highlands of Papua New Guinea and central Australia (hpSahul) [20,22,23,25]. It is also striking that the click-speaking San, former hunter-gatherers whose mtDNA defines a basal lineage for humans, were found to be the original host of hpAfrica2, which, together with the feline H. acinonychis, forms a basal lineage within H. pylori (figure 1e).…”
Section: Helicobacter Pylori and Anatomically Modern Humansmentioning
confidence: 99%
“…A wealth of research since has confirmed that link, with a surfeit of mechanistic data (including the discovery of the H. pylori gene product CagA, a unique bacterial oncoprotein), the development of animal models of H. pyloriinduced cancer, and even some, albeit underpowered, [16,17,34] Other adverse effects of H. pylori A cause of idiopathic thrombocytopenic purpura and (especially in children), obscure iron-deficiency anemia [35,36]. Associated with stunted growth and low IQ in the developing world [37] Whole genome sequencing One of the first genomes to be completely sequenced, enhancing knowledge of H. pylori biology and pathogenesis, with implications for drug and vaccine development [38] Gastric physiology, function and cell turnover Examining the effects of H. pylori eradication improved our understanding of somatostatin/gastrin/gastric acid secretion and regulation [12][13][14] among other aspects of gastric biology, including physiology, microscopic histopathology, cell biology and immunology [21,39] Human evolution Probing the genomic diversity of H. pylori among human populations has informed knowledge of human evolutionary history and migration patterns [40]. The coexistence of mammals with Helicobacter species is widespread, demonstrating an ancient and probably mutually beneficial, relationship…”
Section: Gastric Cancermentioning
confidence: 99%
“…Afin de résoudre cette controverse nous avons récemment analysé 769 souches de H. pylori provenant de 51 populations humaines [11]. Celles-ci ont été génotypées à plus de 1 500 sites variables distribués à travers le génome.…”
Section: L'exemple D'helicobacter Pyloriunclassified